BILINGUALISM AND ITS EFFECTS ON BRAIN FUNCTION (Modern education and development, 2024)
This article is intended to analyse bilingualism and its effects on brain function. Furthermore , this article explores the cognitive, neurological, and social implications of bilingualism, highlighting its benefits and challenges. Bilingual individuals often exhibit enhanced executive functions, improved working memory, and increased brain plasticity, contributing to delayed cognitive decline and greater gray matter density in key brain regions.Supported by scientific studies, this article examines the implications of bilingualism for education, healthcare, and the workplace, emphasizing its transformative impact on brain function and societal integration.